Visions of a better world: Howard Thurman's pilgrimage to India and the origins of African American nonviolence - Dixie, Quinton Hosford (Beacon Press, 2011)
Southern boy, Morehouse man, Rochester scholar -- Starting a career -- Planning the pilgrimage of friendship -- The Negro Delegation in India -- What Thurman learned from India -- Thurman's war and the creation of the Fellowship Church -- Epilogue: Martin Luther King, Jr. and Jesus and the disinherited